Seeking Congruity Between Goals and Roles - Diekman, Amanda B.; Brown, Elizabeth R.; Johnston, Amanda M.; Clark, Emily K. (Psychological Science, 2010)
Although women have nearly attained equality with men in several formerly male-dominated fields, they remain underrepresented in the fields of science, technology, engineering, and mathematics (STEM). We argue that one important reason for this discrepancy is that STEM careers are perceived as less likely than careers in other fields to fulfill communal goals (e.g., working with or helping other people). Such perceptions might disproportionately affect women’s career decisions, because women tend to endorse communal goals more than men. As predicted, we found that STEM careers, relative to other careers, were perceived to impede communal goals. Moreover, communal-goal endorsement negatively predicted interest in STEM careers, even when controlling for past experience and self-efficacy in science and mathematics. Understanding how communal goals influence people’s interest in STEM fields thus provides a new perspective on the issue of women’s representation in STEM careers.